Determinan Minat Menggunakan Aplikasi Kredivo Paylater - Andre Golioth; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine the effect of perceived convenience, perceived benefits, perceived security and intention to use the kredivo paylater application as the dependent variable. The sample in this study was 100 respondents through questionnaires with simple random sampling technique. In this study, descriptive analysis and multiple linear analysis became methods for data analysis with the help of statistical software STATA version 17. The results of this study indicate that perceived ease of use has a positive and significant influence on the intention to use credivo paylater. Meanwhile, perceived usefulness and perceptions of security do not have an influence on the interest in using the paylater credit in the employee class students of the management study program, the faculty of economics and business. Keywords: perceived ease of use, perceived usefulness, perceived security, intention to use